2000
DOI: 10.1038/35003535
|View full text |Cite
|
Sign up to set email alerts
|

Shape control of CdSe nanocrystals

Abstract: Nanometre-size inorganic dots, tubes and wires exhibit a wide range of electrical and optical properties that depend sensitively on both size and shape, and are of both fundamental and technological interest. In contrast to the syntheses of zero-dimensional systems, existing preparations of one-dimensional systems often yield networks of tubes or rods which are difficult to separate. And, in the case of optically active II-VI and III-V semiconductors, the resulting rod diameters are too large to exhibit quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

66
3,503
6
28

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 4,366 publications
(3,603 citation statements)
references
References 30 publications
66
3,503
6
28
Order By: Relevance
“…Besides using size to control their optical and electronic properties, SCNCs can be synthesized in a variety of shapes and dimensionalities (see below);17, 18, 19, 20, 21, 22 these characteristics govern the polarization and the directionality of the emission of the NCs. The surface of the NCs is easily processed, and hence NCs can be introduced onto various phases/substrates such as hydrophobic or hydrophilic media, and onto or into flexible or rigid substrates 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…Besides using size to control their optical and electronic properties, SCNCs can be synthesized in a variety of shapes and dimensionalities (see below);17, 18, 19, 20, 21, 22 these characteristics govern the polarization and the directionality of the emission of the NCs. The surface of the NCs is easily processed, and hence NCs can be introduced onto various phases/substrates such as hydrophobic or hydrophilic media, and onto or into flexible or rigid substrates 23, 24, 25, 26.…”
Section: Introductionmentioning
confidence: 99%
“…18 Nearly spherical to rod-like shapes are produced using ligands such as hexyl phosphonic acid. 19 Aspect ratio is sensitive to phosphonic acid alkyl chain length; the shorter the chain, the more elongated and branched are the nanorods. 18,20 Aspect ratio control has been studied for ZnS, ZnSe,16,21 ABSTRACT We demonstrate molecular control of nanoscale composition, alloying, and morphology…”
Section: Introductionmentioning
confidence: 99%
“…Actually, controlled synthesis of nanostructured materials has been achieved by many solution-based methods [40 45]. For example, Peng et al demonstrated that control of the growth kinetics of the II IV semiconductor CdSe via adjusting monomer concentration could be used to vary the shapes of the resulting particles from a nearly spherical morphology to a rodlike one, with aspect ratios as large as ten to one [46]; the O'Brien group synthesized monodisperse MnO nanocrystals by thermal decomposition of manganese acetate in the presence of oleic acid at 320 °C and showed that the particle size could be adjusted from 12 to 20 nm by controlling the aging time [47]; Hyeon and co-workers also reported a one nanometer-level diameter-controlled synthesis of monodisperse magnetic iron oxide nanocrystals obtained by seed-mediated growth of previously synthesized monodisperse nanoparticle seeds [48]. Although these exciting results provide effective strategies for the synthesis of nanocrystals with controllable shape and size, what is still required is much more rational control over the nanocrystals, namely, the ability to design and optimize nanostructures at will.…”
mentioning
confidence: 99%